The discovery of ATL field expansion in 40 yrs - Yodoi, Junji (Henry Stewart Talks, 2007)
Life cycle of retroviruses, Diseases derived from retroviruses, Adult T-cell leukemia and HTLV-1 retrovirus, ADF/TRX upregulation in HTLV-I T-cell and EBV B-cell transformation, Regulation of thioredoxin gene expression, TRX TG and KO mice, The thioredoxin system, MIF/GIF, Inflammatory response, TBP2: tumor suppressor for HTLV-I leukemia, Clinical trials for inflammatory diseases
Archived at 2021/02/25